Cirsoid arteriovenous malformation of kidney presenting as a mass suggestive of malignancy - (:unkn) unknown (Blackwell Publishing, 1998)
This paper reports a rare case of cirsoid renal arteriovenous malformation (AVM) that showed radiological characteristics of a renal malignancy. Using only conventional procedures such as computerized tomography, the present case was misdiagnosed as a solid tumor mass and therefore radical nephrectomy was indicated. Angiographic analysis is expected to improve the accuracy of diagnosis of AVM, thus reducing the need to resort to invasive techniques.
Keywords: Diagnosis; Renal neoplasms; Vascular malformations